Hardcore Visual Basic - McKinney, Bruce, 1953-. (Redmond, Wash. : Microsoft Press, 1995)
The spirit of Basic; The second level of Basic enlightenment; Basic tolls the Old-Fashioned way; An object way of Basic; Taking control of Windows; Painting pictures; A handle on data; Don't write the same code twice; Stir-fry; The Ole gospel; The new frontier.
Covers version 4.
Keywords: Computers; Microsoft Visual BASIC; BASIC (Computer program language)